2019
DOI: 10.1111/add.14615
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental attitudes and children's alcohol use: a systematic review and meta‐analysis

Abstract: AimsThe main aim was to assess the relationship between parental attitudes towards children's alcohol use and their child's alcohol use. Secondary aims included assessing the relationship between attitudes reported by parents and those perceived by children, and between perceived parental attitudes and children's alcohol use. Methods Meta-analysis of studies reporting on the associations between parental attitudes towards children's alcohol use and children's self-reported alcohol use. Published, peerreviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 74 publications
(227 reference statements)
2
13
0
Order By: Relevance
“…This study shows that family environment factors, including parents' attitudes, behavior, and companionship are related to children's drinking behavior. The study supports that family supervision is negatively correlated with adolescent drinking, which is consistent with the results of other foreign studies ( 19 , 28 ). And this study proved evidence to support this conclusion in the China.…”
Section: Discussionsupporting
confidence: 92%
“…This study shows that family environment factors, including parents' attitudes, behavior, and companionship are related to children's drinking behavior. The study supports that family supervision is negatively correlated with adolescent drinking, which is consistent with the results of other foreign studies ( 19 , 28 ). And this study proved evidence to support this conclusion in the China.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, it is known that when parents have healthy habits or do not support their children's alcohol intake, they have a lower consumption [76]. In addition, alcohol consumption is reduced to a greater extent among children of parents who have a restrictive attitude towards the access to alcohol [77]. Therefore, parents have a fundamental role in preventing and reducing their children's alcohol consumption [38,76,78].…”
Section: Correlation Between Parental Support Factors Age and Gender With The Variable Of Alcohol Consumptionmentioning
confidence: 99%
“…Fourth, although consistent with effect sizes reported in the literature (e.g., Gunn & Smith, 2010; Jackson, Colby et al, 2015), our observed effects were small in magnitude, explaining no more than 3% of the variance in sipping altogether. The existing literature points to several other factors important in the development of sipping, which can be organized into at least five sets of factors: (a) dispositional and psychopathological characteristics like the ones we explored, (b) demographic characteristics, which include being male, White, and participating in a religion where alcohol consumption is at least somewhat religiously sanctioned (Lisdahl et al, in preparation); (c) physical context, including within-home alcohol availability and allied parenting practices that provide exposure to alcohol (e.g., asking the child to fetch or open an alcoholic beverage; Jackson et al, 2013; Jackson, Colby et al, 2015; Tael-Öeren, Naughton, & Sutton, 2019) or encourage consumption of alcohol (Wadolowski et al, 2015); (d) other “proximal” factors, such as drinking motives and alcohol expectancies; and (e) other social or contextual factors, including perceived sibling and peer (Trucco, Colder, & Wieczorek, 2011) approval of drinking, general peer delinquency, and general parental monitoring, warmth, control, support, and conflict (Donovan & Molina, 2008; Jackson, Colby et al, 2015).…”
Section: Discussionmentioning
confidence: 99%